1981
DOI: 10.1136/jnnp.44.12.1165
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid adenosine 3',5'-monophosphate, 5-hydroxyindoleacetic acid and homovanillic acid in patients with sleep apnoea syndrome

Abstract: SUMMARY Adenosine 3',5'-monophosphate (cyclic AMP), 5-hydroxyindoleacetic acid (5-HIAA) and homovanillic acid (HVA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Therefore, it is possible that daytime somnolence might be responsible, at least in part, for abnormal ERP fi ndings in OSAS. It has been suggested that one possible explanation for the observed changes in cognitive evoked potentials could be the presence of changes in neurotransmitter metabolism associated with sleep apnea (Rumbach et al , 1991 ); in fact, it has been shown that 5-hydroxyindoleacetic acid levels were increased in the cerebrospinal fl uid of OSAS patients (Cramer et al , 1981 ), and that P3 latencies may be modifi ed by drugs acting on various neurotransmitters (Kales et al , 1985 ). There is also a report of signifi cant correlations between P3 amplitude and sleep stage 1, sleep effi ciency, MSLT and MWT scores (Sangal and Sangal , 1997a ).…”
Section: Response To Treatment Studiesmentioning
confidence: 99%
“…Therefore, it is possible that daytime somnolence might be responsible, at least in part, for abnormal ERP fi ndings in OSAS. It has been suggested that one possible explanation for the observed changes in cognitive evoked potentials could be the presence of changes in neurotransmitter metabolism associated with sleep apnea (Rumbach et al , 1991 ); in fact, it has been shown that 5-hydroxyindoleacetic acid levels were increased in the cerebrospinal fl uid of OSAS patients (Cramer et al , 1981 ), and that P3 latencies may be modifi ed by drugs acting on various neurotransmitters (Kales et al , 1985 ). There is also a report of signifi cant correlations between P3 amplitude and sleep stage 1, sleep effi ciency, MSLT and MWT scores (Sangal and Sangal , 1997a ).…”
Section: Response To Treatment Studiesmentioning
confidence: 99%
“…16 18 In support of terminal exhaustion of serotonin are the findings of increased levels of serotonin metabolites in the cerebrospinal fluid. 19 Cann-Moisan 20 found that several neurotransmitters and metabolites were increased in the cerebrospinal fluid of SIDS victims compared with living controls; they also found high levels of these in cerebrospinal fluid in infants after they had survived severe asphyxia.…”
Section: Vulnerable Infantmentioning
confidence: 99%
“…In patients suffering from sleep obstructive apnoea, increases in the levels of the inactive catabolite (5-hydroxyindoleacetic acid) were reported to occur (Cramer, Warter, Renaud, Krieger, Marescaux & Hammers, 1981) and might be attributable to an abnormally high level of 5-HT release. Furthermore, 5-HT has been assumed to play a role in sleep regulation, since tryptophan may restore the capacity to sleep in animals with 5-HT-depleted raphe neurons (for review see Vogt, 1982) and 5-HT2 antagonist modifies human sleep (Idzikowski, Mills & Glennard, 1986).…”
Section: Indirect Effectsmentioning
confidence: 99%